Arts and health: active factors and a theory framework of embodied aesthetics - Koch, Sabine C. (The arts in psychotherapy, 2017)
This article provides an approach to central specific active factors effective in the arts therapies that (a) can be distinguished from therapeutic factors present in other medical treatments and psychotherapies, and (b) that can be assumed to work as mechanisms of effectiveness across the arts. In the absence of a current aesthetic model for the arts therapies from psychology or the cognitive sciences that includes active art-making, a theory framework of embodied aesthetics is suggested that encompasses the active (expression) and the receptive (impression) aspects of the aesthetic experience. Five specific factors of arts therapies are identified: aesthetics, hedonism, nonverbal communication/metaphor, enactive transitional support and generativity. Aesthetics, including beauty and authentic expression, is considered to be the most specific arts therapy factor. The framework presented grounds the question of active factors in an embodied enactive model of the aesthetic experience, in which art-making is considered alongside art perception.